Time-Tangent Surfaces Around Biharmonic Particles and Its Lorentz Transformations in Heisenberg Spacetime - Körpınar, Talat; Turhan, E. (My University, 2013)
In this work, we introduce a new spacetime using Heisenberg group and call this space as "Heisenberg spacetime". We give a geometrical description of time-tangent surfaces around timelike biharmonic particle in H14. Moreover, we obtain Lorentz transformations this particles. Additionally, we illustrate our results in Figs. 1-6. © 2013 Springer Science+Business Media New York.
Keywords: Bienergy; Energy; Faraday tensor; Heisenberg group; Lorentz transformations